(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Swami Vivekananda, a prominent Indian philosopher and spiritual leader of the late 19th century, played a pivotal role in introducing Vedanta philosophy to the Western world. His comprehensive interpretation and presentation of Vedanta philosophy continue to inspire seekers of truth and scholars alike. This abstract offers a brief philosophical review of Swami Vivekananda’s contributions to Vedanta philosophy. Vedanta is one of the six orthodox schools of Indian philosophy and is primarily concerned with understanding the nature of reality (Brahman) and the relationship between the individual soul (Atman) and the ultimate reality. Swami Vivekananda’s interpretation of Vedanta philosophy is characterized by its accessibility, inclusivity, and relevance to the contemporary world.One of Swami Vivekananda’s central teachings is the concept of oneness or Advaita, which asserts that the ultimate reality, Brahman, is devoid of all distinctions and that the individual soul (Atman) is not separate from Brahman but an intrinsic part of it. This idea of non-duality has profound implications for understanding the interconnectedness of all beings and the unity of existence.Swami Vivekananda emphasized the practical application of Vedanta philosophy in daily life. He believed that spirituality should not be divorced from the material world, and that true spiritual realization could be attained through selfless service (Karma Yoga), devotion (Bhakti Yoga), and meditation (Dhyana Yoga). His teachings advocated a holistic approach to life, blending the pursuit of spiritual wisdom with social and humanitarian concerns. Furthermore, Swami Vivekananda’s message transcends the boundaries of religion and culture. He envisioned Vedanta philosophy as a universal truth that could be embraced by people of all backgrounds, promoting the idea of religious pluralism and tolerance. His famous address at the World’s Parliament of Religions in Chicago in 1893 introduced Vedanta to a global audience, emphasizing the universality of spiritual principles. In conclusion, Swami Vivekananda’s philosophical review of Vedanta philosophy is a profound exploration of the nature of reality, the self, and the human experience. His teachings emphasize the unity of all existence, the practical application of spiritual principles, and the universal appeal of Vedanta. His legacy continues to inspire individuals seeking spiritual insight and a deeper understanding of the timeless wisdom contained in Vedanta philosophy